In our dreams - Lael Miller, Linda (Zebra Books, 1998)
In the contemporary thriller, never been to Anphar, a mysterious undercover agent, who deliciously resembles Harrison Ford, rescues a woman from terrorists. In Bridge of dreams, a lonely french teacher travels to Paris to see if the man she once loved, who could be Daniel Day-Lewis´s double, remebers a promise made a decade before.